Effect of Vitamin C to The Plasma Level of Interleukin-6, Plasma MDA and Length of Hospitalization of COPD Exacerbation Patient - Fadlia Yulistiana; Suradi Suradi; Reviono Reviono (Jurnal Respirologi Indonesia, 2018)
Background: Exacerbation is an acute condition characterized by worsening of symptoms that require a change in therapy. Increased inflammation of the airways and lungs during exacerbations causes an increase in plasma IL-6 and MDA levels and causes most patients needed treatment at the hospital. Vitamin C is an antioxidant vitamin that has anti-inflammatory and antioxidant effects so that it can be added to COPD exacerbations therapy. This study aims to determine the effect of vitamin C on plasma IL-6, plasma MDA levels and length of hospitalization of acute exacerbation of COPD patients. Methods: This research is an experimental study with pre-test and post-test design. Subjects consisted of 33 patients with exacerbation of COPD were treated at the Soehadi Pridjonegoro Hospital Sragen in October-November 2015 which were selected by purposive sampling. Subjects were divided into two groups, the treatment group (n=16) received vitamin C therapy 1x1000 mg/day and the control group (n=17) received 5 mL of NaCl 0.9%. Levels of IL-6 plasma and plasma MDA was measured on admission and at discharge criteria are met. Length of hospitalization is calculated based on the number of days’ patients in hospital. Results: There was no statistically significant difference to decreased of IL-6 plasma level (P=0.379), MDA plasma level (P=0.27) and length of hospitalization (P=0.24) between treatment and control group. Conclucions: The addition of vitamin C 1x1000 mg/day during hospitalization is not helpful to decreased in levels of plasma IL-6, plasma MDA and length of hospitalization in this study. (J Respir Indo 2018; 38(1): 24-32)